2021
DOI: 10.1039/d1cp03023j
|View full text |Cite
|
Sign up to set email alerts
|

σ–Hole activation and structural changes upon perfluorination of aryl halides: direct evidence from gas phase rotational spectroscopy

Abstract: Enhancement of the σ-hole on the halogen atom of aryl halides due to perfluorination of the ring is demonstrated by use of the Extended Townes−Dailey (ETD) model coupled to a...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…[ 41 ] The I 3d peaks are shifted to the lower binding energy after ATFC modification (Figure 3b), which is induced by the F···I non‐covalent interaction that is different from the halogen bond because the positively charged σ ‐hole center cannot be formed in ATFC. [ 42 ] The XPS experiments of O 1s, N 1s, and F 1s are performed to reveal the reason for the movement of Pb 2+ peaks. According to Figure 3c–e, with the addition of PbI 2 , the movement of O 1s (1.01 eV, from 530.42 to 531.43 eV) is far larger than that of F 1s (0.38 eV, from 687.38 to 687.76 eV) and N 1s (0.15 eV, from 399.65 to 399.80 eV), suggesting that the Lewis acid–base interaction between CO and undercoordinated Pb 2+ is stronger than that of the coordination interaction of NH 2 ···Pb and the electrostatic interaction of FPb.…”
Section: Resultsmentioning
confidence: 99%
“…[ 41 ] The I 3d peaks are shifted to the lower binding energy after ATFC modification (Figure 3b), which is induced by the F···I non‐covalent interaction that is different from the halogen bond because the positively charged σ ‐hole center cannot be formed in ATFC. [ 42 ] The XPS experiments of O 1s, N 1s, and F 1s are performed to reveal the reason for the movement of Pb 2+ peaks. According to Figure 3c–e, with the addition of PbI 2 , the movement of O 1s (1.01 eV, from 530.42 to 531.43 eV) is far larger than that of F 1s (0.38 eV, from 687.38 to 687.76 eV) and N 1s (0.15 eV, from 399.65 to 399.80 eV), suggesting that the Lewis acid–base interaction between CO and undercoordinated Pb 2+ is stronger than that of the coordination interaction of NH 2 ···Pb and the electrostatic interaction of FPb.…”
Section: Resultsmentioning
confidence: 99%
“…Relativistic effects are likely to play a role for Br, while Cl should be largely unaffected as previous studies have shown. [82][83][84] To this end, relativistic calculations have been conducted using the Douglas-Kroll-Hess of second order (DKH2) [85][86][87] transformation. For these calculations, the finite nucleus model 88 and picture change effects 89 are included.…”
Section: Methodsmentioning
confidence: 99%
“…As regards the P -population anisotropy, two series of data are derived: one from the calculated χ (Δ P zz χ ) and the other from the NBO analysis of the p-orbitals population (Δ P zz NBO ). As already discussed, , the positive value of Δ P zz is a direct measure of the strong electron density along the z -axis, while a negative value indicates a deficiency of electron density (σ-hole) which could lead to interaction with a nucleophilic group. The value of Δ P zz decreases going from the monomer to the complex for C 6 F 6 –NH 3 .…”
mentioning
confidence: 92%